Estudo de prevalência da esquistossomose mansônica no bairro do Maracajá, distrito de Mosqueiro, Belém, Pará - MALCHER, Sérgio Alexandre Oliveira (Universidade Federal do Pará, 2013)
Schistosomiasis mansoni is one of the most widespread parasitic diseases in the world and has a higher prevalence in developing countries, and is currently a serious public health problem in Brazil. In Belém-PA, District Administrative Mosqueiro (DAMOS), there are possibilities of occurrence of autochthonous cases of schistosomiasis mansoni, due to geographical proximity to other areas where there are records of this disease, as well as the presence of other environmental risk factors, as the presence of Biomphalaria straminea. With the proposal to determine the prevalence of schistosomiasis mansoni in the neighborhood of Marazion-DAMOS, a cross-sectional study was conducted prospectively between March 2011 and January 2012, through parasitological survey by the quantitative method of Kato- Katz, associated with social inquiry demographic and environmental location. Participated in the sampling universe included 407 individuals in the care of the Family Health Strategy, which voluntarily agreed to participate in the survey, according to the ethical regulations. The socio-demographic profile of the population was mainly aged between 11 and 40 years without gender differences, whose occupation of housewife and student, with incomplete primary education were the most cited. Most residents were born and proceeds from the DAMOS, residents in the neighborhood of Marazion for over 20 years, without reports of significant displacement to other locations. Most households had piped water service, with indoor bathroom, toilet presence of bound stools in the septic tank. Water collections peridomestic ditches were characterized by low flow and small water flow, high concentration of organic products, the presence of vegetation and macrófitica vector Biomphalaria straminea. This population reported having no contact with the water collection and know the planorbid vector, as well as the very schistosomiasis The investigation has resulted in 100% parasitological blade negative and the identification of eggs of S. mansoni, leading to the conclusion that although the neighborhood of Marazion is still harmless, several factors have to install a focus of active transmission of schistosomiasis, but there is still a fragile ecological balance, supported by the reduced exposure of individuals to water collection, bit shift population to areas with established foci of endemic and reasonable coverage of sanitation. This set of variables has acted as limiting factors to the process of endemic schistosomiasis in the neighborhood of Marazion, however, must be kept under surveillance by the peculiarities conducive to closing the cycle of S. mansoni.